Photoluminescence Response in Carbon Films Deposited by Pulsed Laser Deposition onto GaAs Substrates at Low Vacuum. (10th November 2016) - Caballero-Briones, F.; Santana, G.; Flores, T.; Ponce, L.
Abstract : Carbon films were deposited onto GaAs substrates by pulsed laser deposition at low vacuum (10–15 mTorr) from a graphite target. Films were prepared at different number of pulses (1500 to 6000) with fixed fluence (32 J/cm 2 ), target-to-substrate distance, and pulse frequency using a Q:Switched Nd:YAG laser at 1064 nm operating at a frequency of 10 Hz and producing burst-mode pulses with total duration per shot of 49 ns. Films were characterized by optical microscopy, atomic force microscopy, laser induced breakdown spectroscopy, X-ray diffraction, and photoluminescence spectroscopy. Deposited films were visually smooth and adherent but on the other hand evidence of splashing was observed in all the films. Thickness varied linearly with the number of pulses from 8 to 42  μ m with maximum height differences around 700 nm. Hexagonal and orthorhombic carbon was found in all the films and there was no evidence of nitrogen or oxygen incorporation during ablation process. Broad photoluminescence bands were observed and, particularly, emission peaks at 475–480 nm, 540–550 nm, 590 nm, and 625 nm. Bands tend to shift to lower wavelength with film thickness, suggesting that luminescence comes from splashed nanostructures influenced by the semiconducting substrate. This particular substrate effect is vanished as thickness of the films increases.